فصاحة القرآن الثابتة والتطور اللغوي المتغير - Ali Burhan (LISANIA: Journal of Arabic Education and Literature, 2017)
Fashahah according to the classic scholars is sealed by period, place, and vocabularies with certain conditions, while it according to contemporary scholars is a process of renewable development. In modern linguistics, it reveals the activities and thought of the modern Arab nation. It  continuously describes its function as a different transmitter of the Arabic functions according to classic scholars which is more dynamic and not static. The result concludes that the classical Arab in the Qur'an is in peak not only as a means of conveying the thought, but also becomes the religious and unifying language of Arab nations with its various specifications. The process of evolution occurring in Arabic Language includes its pronunciation, structure of grammar, and dilalah.